2011
DOI: 10.1007/s12070-011-0307-6
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Risk Factors and the Identification of Hearing Loss in Infants

Abstract: To identify potential risk factors for hearing loss from the infant with high risk criteria as guided by the Joint Committee on Infant Hearing (JCIH, 2000). 490 infants with age range of 2 days to 6 months who had undergone detailed audiological evaluation during for the period of 3 years at Gauhati Medical College Hospital were taken for the study. The hearing screening was performed on each infant using Distortion Product Otoacoustic Emission (DPOAE) testing. The infants who failed DPOAEs screening were foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…This finding was similar to another study done in Gauhati Medical College Hospital, India. [18] Similar to another study by Pisani F et al [15] this study also showed association of multiple episodes of seizure with poor neurologic outcome including vision and hearing loss.…”
Section: Discussionsupporting
confidence: 84%
“…This finding was similar to another study done in Gauhati Medical College Hospital, India. [18] Similar to another study by Pisani F et al [15] this study also showed association of multiple episodes of seizure with poor neurologic outcome including vision and hearing loss.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, ototoxic medication was the most frequent risk factor, followed by hyperbilirubinaemia, prematurity, mechanical ventilation, low birth-weight, and post-genital infections. These factors were the most frequently observed in high risk infants for HL; also in other trials with predominance of low birth-weight, prematurity, and ototoxic drug administration [17][18][19]. However, the frequent existence of a specific risk factor does not necessarily mean that this factor has any causative effect to the outcomes of screening.…”
Section: Risk Factor *Nh(%) [N=163] **Ansd (%) [N=7] ***Hl (%) [N=3] Pmentioning
confidence: 90%
“…11 Infections that can cause hearing disorders such as bacterial meningitis, intrauterine infections (CMV, rubella, herpes, syphilis, and toxoplasmosis). 14 The least health risk factors during the prenatal period were hypertension [2 patients (6.7%)] and medications used [2 patients (6.7%)]; in natal period was premature [3 patients, (10%)] and baby born without crying [3 patients, (10%)]. History of the use of herbs or medicines was also reported in Palembang although the type of herbs or medicines taken by patients are not cleared.…”
Section: Discussionmentioning
confidence: 99%